Archetypes in Today’s Advertising - Ioana Aida Furnica Slusaru (Anastasis: Research in Medieval Culture and Art)
This paper explores ancient myth and mythological figures in contemporary advertising as a means of communication with consumers. In a hermeneutical and analytical way, through psychologic and semiotic theories, we classify and analyze the most recurrent themes: mythical time; beauty and eternal youth; success and power; idyllic environment, the search for the lost paradise. Based on universal archetypes, we see how advertising becomes an excellent vehicle to effectively reach the receiver’s subconscious and act as an inciter to consumption.